Animal biodiversity conservation in managed forests: possible role of the defaunation in the recruitment of forest species in Sarapiqui, Costa Rica - Rosales Adame, J.J. (CATIE, Turrialba (Costa Rica), 2014)
15 fig. 5 tab. Bib. p. 83-89. Sum. (En, Es)